Effect of grass-legume silage on production and milk composition of Friesian cross cows in Imbo region of Burundi - Ahimpera, Francine; Munyaneza, Napoleon; Albert, Iribagiza; Manyawu, Godfrey Jabulani; Nyabongo, Lionel; King'ori, Anthony Macharia (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study determined the effects of feeding Cenchrus purpureus- Velvet bean, or Maize stalk- Velvet bean silage on milk production and quality. The one-way analysis of variance (ANOVA) in R4.4.1 software was used for data analysis. Results from the study showed that there was a significant difference (P < 0.01) in milk production among treatments. The mean milk production was different between the blocks (P < 0.05). The mean milk production was higher (7.53±1.52 kg) for cows fed on maize stalk-Velvet bean silage than cows fed on Cenchrus purpureus-Velvet bean silage (5.36±1.07 kg) and fresh mixed grass-legume (4.29l±1.07 kg). Results also showed a significant difference (p<0.05) in milk SNF, lactose and salt, while there were no significant differences (p˃0.05) on milk fat and protein contents for all the experimental diets. The study concluded that the incorporation of maize stalk: Velvet bean silage ratio (80:20) could prevent the dry season feed scarcity, increase milk production and consequently increase the household income. Int. J. Agril. Res. Innov. Tech. 15(1): 48-53, June 2025